Lipophosphonoxins: new modular molecular structures with significant antibacterial properties - Rejman, Dominik; Rabatinová, Alžbeta; Pombinho, António R; Kovačková, Soňa; Pohl, Radek; Zborníková, Eva; Kolář, Milan; Bogdanová, Kateřina; Nyč, Otakar; Sanderová, Hana; Látal, Tomáš; Bartůněk, Petr; et al. (Journal of medicinal chemistry, 2011)
Novel compounds termed lipophosphonoxins were prepared using a simple and efficient synthetic approach. The general structure of lipophosphonoxins consists of four modules: (i) a nucleoside module, (ii) an iminosugar module, (iii) a hydrophobic module (lipophilic alkyl chain), and (iv) a phosphonate linker module that holds together modules i-iii. Lipophosphonoxins displayed significant antibacterial properties against a panel of Gram-positive species, including multiresistant strains. The minimum inhibitory concentration (MIC) values of the best inhibitors were in the 1-12 μg/mL range, while their cytotoxic concentrations against human cell lines were significantly above this range. The modular nature of this artificial scaffold offers a large number of possibilities for further modifications/exploitation of these compounds.
Keywords: Hydrophobic and Hydrophilic Interactions; erytroidní prekurzorové buňky; Drug Resistance, Multiple, Bacterial; viabilita buněk; Organophosphonates; Erythroid Precursor Cells; Nucleosides; hydrofobní a hydrofilní interakce; mnohočetná bakteriální léková rezistence; Structure-Activity Relationship; antibakteriální látky; nukleosidy; Microbial Sensitivity Tests; Cell Survival; grampozitivní bakterie; fetální krev; Fetal Blood; vztahy mezi strukturou a aktivitou; kultivované buňky; stereoizomerie; lidé; Gram-Positive Bacteria; Anti-Bacterial Agents; Humans; organofosfonáty; mikrobiální testy citlivosti; apoptóza; Cells, Cultured; Apoptosis; Stereoisomerism